MEKANISME PENGAWASAN TITIK-TITIK REKLAME DI KAWASAN SIMPANGLIMA KOTA SEMARANG - Bayu Indra Permana; Puji Astuti; Sulistyowati . (Journal of Politic and Government Studies, 2014)
Simpanglima function as a public space in accordance with Regulation No. 14 Year 2012Article 4 Paragraph 4 ( a) that menyebutan